STUDY OF THE EFFICACY AND SAFETY OF IV CARNITINE IN CHF - K. SOLOMON RAJU M.D. (International Journal of Pharma and Bio Sciences, 2014)
Congestive Heart Failure (CHF) is one of the most prevalent public health problem of today. CHF is not a disease but a condition that occurs when the heart is unable to pump enough blood to meet the needs of body’s tissues. Deficient myocardial Carnitine levels are also involved in the pathogenesis of CHF. Various inotropic drugs, diuretics and vasodilators used in treatment improved the condition of CHF patients to some extent. In this present study, efficacy and safety of Carnitine in CHF is evaluated. It is observed that administration of 2gms of IV L-Carnitine/day improved the condition of CHF patients with beneficial effects characterized by significantly increasing Ejection fraction (P<0.001). It stimulates the cardiac metabolism and increases the coronary blood flow and decreases ventricular dilation and reduces triglyceride levels significantly (p<0.001).